DETERMINAN UNDERPRICING INITIAL PUBLIC OFFERING (IPO): FAKTOR FUNDAMENTAL, PASAR, DAN INSTITUS – A SYSTEMATIC LITERATURE REVIEW - Muhammad Razan; Totok Dewayanto (Diponegoro Journal of Accounting, 2026)
IPO underpricing refers to a condition where the initial offering price is lower than the first-day closing price in the secondary market. This phenomenon is important because it relates to fundraising efficiency, pricing accuracy, and information asymmetry between issuers and investors. This study aims to identify and synthesize the determinants of IPO underpricing based on fundamental, market, and institutional factors.This research employs a Systematic Literature Review (SLR) method using Scopus-indexed journal articles published between 2020 and 2025. From an initial 792 articles, 30 eligible studies were selected through identification, screening, and relevance analysis.The findings indicate that IPO underpricing is influenced by the interaction of multiple factors. Fundamental factors, such as firm size, profitability, leverage, and firm age, affect investors’ risk perceptions. Market factors, including hot market conditions, investor sentiment, and market volatility, shape market expectations and initial returns. Institutional factors, such as corporate governance, ownership structure, underwriter reputation, and political connections, also play important roles as certification mechanisms. Overall, IPO underpricing should be understood as a multidimensional phenomenon shaped by firms’ internal conditions, market dynamics, and institutional quality. This study contributes by providing an integrated and structured synthesis of recent empirical findings on IPO underpricing.